Frequency of Morbidly Adherent Placenta in Previous Scar - Nissa, Fakhar Un; Dars, Saira; Awan, Shazia; Mumtaz, Firdous (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To assess the frequency of different types of morbidly adherent placenta in woman presenting history of previous scar. METHODOLOGY: This descriptive cross-sectional study was conducted from December 2016 to June 2017 at Department of Obstetrics & Gynaecology, Indus Medical College Hospital Tando Muhammad Khan & Liaquat University of Medical & Health Sciences Jamshoro. A total of 205 patients with age women between 15 to 49 years, with having pregnancy of 04 to 36 weeks, alive singleton fetus, history of previous surgery like Caesarean Section, myomectomy, hysterotomy and associated placenta praevia were included. Patients with history of pelvic inflammatory disease (PID), dilatation and curettage (D&C) and intrauterine contraceptive device (IUCD) insertion, placenta abruption and primigravida were excluded. Mean+SD, frequencies & percentages were calculated. Chi-square test was used as a test of significance with a P value <0.05. RESULTS: Around 45.4% (n=93) women had scar due to previous caesarean section. Morbidly adherent placenta was found positive among 9.76% (n=20) women. Frequency of Placenta accreta vera was 1.5% (n = 3), Placenta increta was 6.76% (n = 14) and Placenta percreta was 1.5% (n=3). Stratified analysis found that risk of Morbidly adherent placenta (MAP) elevated with the increasing age, second trimester, high parity, having previous caesarean section & shorter the duration of scar. CONCLUSION: Morbidly adherent placenta is not a very uncommon condition. Its frequency is ten times more among women who had previous history of scar. Hence, the previous scared uterus and shorter duration increased further risk for all three types of morbidly adherent placenta.